Optimaliasi Partisipasi Masyarakat dalam Pengkemasan Paket Wisata Desa Tihingan Kabupaten Klungkung - Trimandala, Nyoman Agus; Putra, Dewa Putu Kiskenda Erwanda (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This community service activity was carried out with the aim of optimizing community participation in the packaging of local potential-based tour packages in Tihingan Village. The main problem faced by the partner villages is not optimal utilization of cultural and natural potential due to limited capacity of Human Resources (HR), especially in the aspect of tourism services (hospitality), tour guide techniques, and foreign language proficiency. The This community service implementation method uses a participatory approach which includes initial observations, group discussion forums (FGDs), intensive training, field assistance, and collaborative preparation of tour packages. The results of the activity showed that Tihingan village has excellent potential in the form of traditional gamelan production that is still active, trekking trails, village cycling, and local culinary that can be packaged into an integrated tourism product. Through the mentoring process, three main tour packages were successfully prepared and there was an increase in community capacity and strengthening of local institutions. This Program has an impact on increasing community participation, the formation of a more systematic tourism product, and the growth of collective awareness of the importance of sustainable community-based tourism management